The remix : how to lead and succeed in the multigenerational workplace - Pollak, Lindsey (HarperBusiness, 2019)
"The essential guide for business leaders, entrepreneurs, and employees looking to navigate today's multigenerational workplace, which spans more generations than ever before. Millennials have only just begun their reign as the largest generation in the workplace. But they are not alone. For the next decade at least, these young professionals will be working side by side with more established generations, including the Baby Boomers who are working longer than ever, and an entirely new group coming up, Generation Z. This means within any organization, any team, any meeting, any marketing opportunity, you may find any combination of generations. Each of these age groups has their own attitude, expectations, and professional style. To lead and succeed in any organization today, you must adapt to how Millennials work, while continuing to accommodate their older colleagues and paying attention to the next generations coming up. The Remix shows you how to adapt and win through proven strategies that serve all generations' needs. As the leading expert on generations in the workplace, Lindsey Pollak combines the most recent data from a variety of authoritative sources with her own original research, as well as detailed case studies from her Fortune 500 clients. Pollak outlines the ways businesses, executives, mid-level managers, employees, and entrepreneurs can handle situations that may arise when diverse styles clash and provides clear strategies to turn generational diversity into business opportunity. Generational change is impacting all industries, all types of organizations, and all leaders. The Remix is an essential read for anyone who wants to survive and thrive today and into the future"--